WSA206, a paralog of duplicated MPF2-like MADS-box family is recruited in fertility function in Withania. (December 2016) - Khan, Muhammad Ramzan; Ihsan, Humera; Ali, Ghulam Muhammad
Highlights: For the first time using functional genomics approaches in wild plant Withania of Solanaeae family, we are able to show that WSA206 (MPF2-like) protein of MADS-box family is controlling male fertility in this plant. This protein interacts with various other MADS-box and non MADS-domain proteins reported to be involved in fertility trait. We have also shown that the WSA206 CDS and 5′ regulatory sequence conserve some distinctive cis -motifs such as GAAATTGTTA controlling gene expression in plant male reproductive tissues, and are capable of directing anther-specific gene expression. Furthermore, another important finding of this study is that fertility and calyx inflation are tightly coupled traits. Since a number of cytotoxic genes are available, a potential application of WSA206 and its promoter is to engineer male sterility for hybrid production of various crop plants. From applied perspective, this will provoke the scientists to study fertility mechanism for creating CMS lines to be used in hybrid production. Our study will inspire the scientists to study the role of gene/genome duplications and contribution of cis -regulatory motifs in fertility. Abstract: Best known for their implication in calyx inflation, MPF2-like genes pertinent to the STMADS11 clade of the MADS-box family exert their functions in leaf development, flowering time, inflorescence architecture and floral reversion to just name but a few. However, our knowledge about their involvement in fertility function remained obscure. Therefore the major thrust of this study was to probe the recruitment of WSA206 (MPF2-like) protein in fertility function. The WSA206 functions were revealed by knocking down and overexpressing this protein in Withania somnifera . The WSA206 promoter functions were defined by stable integration in Arabidopsis using GUS tag. The interactions of WSA206 were investigated by screening Arabidopsis Oligo-dT yeast library and YFP-split analysis. WSA206 knockdown plants revealed fewer flowers, abortion in seed set, reduction in pollen number and deformed non-viable pollen in comparison with wild type counterparts. Overexpression of WSA206 in Withania generated more berries/seeds and healthier viable pollen grains. Remarkably, along with fertility control, the impairment in calyx inflation in knockdown Withania plants and extraordinary growth of sepals in overexpression lines is observed. Thus, fertility and calyx inflation are tightly coupled traits under the control of WSA206. Coding sequence revealed SNP mutations from arginine to lysine as well as a leucine-rich motif duplication at the C-terminus, a characteristic feature of pollen specific and fertility function proteins. The protein–protein interaction spectrum of WSA206 comprises 40% of those MADS and non-MADS-box proteins implicated in floral/anther expression and embryogenesis. Predominant WSA206 promoter:GUS expression accrued in the anthers/pollen may be attributed to of the presence of GAAATTGTTA pollen specific proximal motifs along with several other anther specific homotypic cis -clusters. MPF2-like protein WSA206 through interactions with MADS-box and non-MADS-domain proteins confers male fertility in Withania regulated by anther/pollen specific promoter motif GAAATTGTTA.